The merchant bankers - Wechsberg, Joseph (London : Weidenfeld and Nicolson, 1966)
This book contains the story line of the beginning of merchant banking in the small town of Moravia, which was then a province of the Habsburg monarchy. It shows how merchant bankers rose from poverty to riches up till the rise of Lehman Brothers.
usc 25/05/2017
Loans
Keywords: Merchant banking; Banks and banking